AN ANALYSIS OF FEMINISM IN MERRY RIANA : MIMPI SEJUTA DOLAR MOVIE - Fitri Apriyanti; Rahmi Aulia Nurdini (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2021)
In literary works, films cannot be separated from life, one of which discusses the issue of discrimination against women, a phenomenon that continues to be actively debated in society and gave birth to the feminism movement. Feminism can also appear through films, one of which is Merry Riana. Therefore, this paper aims to find out what is meant by feminism and how feminism is reflected in films and associated with liberal feminism. This study uses a qualitative method with sources from the original Merry Riana video. The writer uses data collection techniques from online sources. The data were collected by watching the film and understanding the film's dialogue several times and making observations to strengthen the analysis using the semiotic theory by Charles Sanders Pierce. The results of this study indicate that: (1) 8 data indicate the presence of elements of feminism in Merry Riana's action. (2) Feminism is shown through Signs, Objects and Interpreters. (3) In liberal feminism, it proves that women are not only focused on the private sphere, but can also be in the public sphere. Key words: Literature, Movie, Merry Riana, Feminism